Hemodynamics and Surgical Results of Chronic Venous Insufficiency with Skin Changes in the Lower Limbs - Hoshino, Shunichi; Takase, Shinya; Satokawa, Hirono; Iwaya, Fumio; Igari, Tsuguo; Midorikawa, Hirohumi; Ogawa, Tomohiro (Japanese Journal of Cardiovascular Surgery, 1996)
Preoperative hemodynamics in the lower limbs in 174 limbs of 103 patients were measured and investigated and the surgical results were evaluated. The subjects were divided into the C4-6-group, which included 51 limbs with skin changes, and the C2, 3-group, which consisted of 123 limbs without skin changes. Plethysmography showed that the maximum venous outflow was significantly higher, and the refilling time was shorter in the C4-6-group compared to the C2, 3-group. All C4-6-group patients had reflux of the long saphenous vein, and the reflux velocity and volume was significantly greater than in the C2, 3-group. Limbs with deep vein reflux accounted for 45% of the C4-6-group. We performed angioscopic deep vein external valvuloplasty in 23 of those limbs. There was no case of reccurence of skin changes at a mean follow-up of 22 months. However chronic venous insufficiency often was associated with multisegmental reflux lesions and in such cases it might be necessary to perform multiple surgical procedures to eliminate the reflux.